Proposed method to measure the economic impact of SARS-COV-2 (Dimensión Empresarial, 2020)
The SARS-CoV-2 pandemic has led to the Second Global Crisis, the magnitude and duration of which is expected to be more intense than the First Global Crisis of 2008 caused by the bankruptcy of Lehman Brothers. This paper proposes a procedure to calculate the economic impact of SARS-CoV-2, taking into account the number of deaths by gender by age bracket (40-49, 50-59 and 60-64 years) and the updated value of income per capita moderated by the average of each age bracket. As a result, the social and economic impact of the virus is reflected on.